The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/nrneph.2016.135
|View full text |Cite
|
Sign up to set email alerts
|

The importance of total kidney volume in evaluating progression of polycystic kidney disease

Abstract: The rate at which autosomal dominant polycystic kidney disease (ADPKD) progresses to end-stage renal disease varies widely and is determined by genetic and non-genetic factors. The ability to determine the prognosis of children and young adults with ADPKD is important for the effective life-long management of the disease and to enable the efficacy of emerging therapies to be determined. Total kidney volume (TKV) reflects the sum volume of hundreds of individual cysts with potentially devastating effects on ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 78 publications
2
101
0
Order By: Relevance
“…Autosomal dominant polycystic kidney disease (ADPKD) is the most common of a group of inherited kidney disorders characterized by progressive cyst development and various extrarenal manifestations (1,2). Cystogenesis in the human kidneys can progressively occupy the normal parenchyma of the kidney and lead to renal failure, which usually occurs in mid-to-late adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autosomal dominant polycystic kidney disease (ADPKD) is the most common of a group of inherited kidney disorders characterized by progressive cyst development and various extrarenal manifestations (1,2). Cystogenesis in the human kidneys can progressively occupy the normal parenchyma of the kidney and lead to renal failure, which usually occurs in mid-to-late adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that many promising drugs showed potential therapeutic effects for ADP-KD in a large number of preclinical and clinical trials (1,7,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). However, some of those in clinical trials -these promising drugs included mTOR inhibitors (55,56), somatostatin analogs (57,58), ACEI/ ARB (59,60), and tyrosine kinase inhibitor (61) -did not prevent the decline of EGFR in ADPKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The annual increase in TKV has been estimated to be around 5% 7, 10 per year, suggesting that TKV measurement should be accurate to capture small changes over time. The most commonly used methods for kidney volume computation such as manual delineation and stereology 13 are simple but time consuming and subject to intra/inter-observer variability.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have used changes in TKV as a primary endpoint [9,12]. The role of TKV in evaluating ADPKD progression and its possible role as a surrogate endpoint in randomized clinical trials has also been reviewed [18]. However, some studies have indicated a lack of correlation between TKV growth rate and decline in renal function [19,20], leading to discussions regarding the use of TKV as a secondary endpoint.…”
Section: Introductionmentioning
confidence: 99%